Similarity in Consumption Patterns among Peasant Communities in Roman Central Hispania through Network Science - Fernando Moreno-Navarro (Journal of Computer Applications in Archaeology, 2024)
This research investigates the consumption patterns of Roman non-elite rural communities in Central Hispania from the 1st to the 3rd century AD. Using similarity metrics, specifically Brainerd-Robinson analyses in artefact type co-presence networks, the study delves into the consumption patterns among these settlements, providing new insights into their local integration. A notable pattern emerges, revealing marked consumption similarities among these communities, suggesting access to shared trade networks and a common cultural framework. Yet, amidst these commonalities, instances of resilience against total cultural homogenisation are noted, exemplifying the local cultural adaptations in response to Roman homogenisation.